Optimization of Dikmas Lantas Unit Kamsel of Grobogan Police in Preventing Traffic Violation - Wahyudi, Kevin (Advances in Police Science Research Journal, 2024)
Due to the number of traffic violations that occurred in the jurisdiction of Grobogan has increased again. Even though since 2018 the number of traffic violations has started to decline in Grobogan until 2021. Dikmas Lantas has been carried out by members of the Kamsel Lantas Unit of the Grobogan District Police but cannot prevent the number of traffic violations from increasing. So the author conducted a study to observe the implementation of Dikmas Lantas by the Kamsel Unit of the Grobogan Traffic Police in preventing traffic violations. In this study, the approach used is a qualitative approach then this type of research is fieldresearch conducted in Grobogan Regency. The focus of this research is the optimization of Dikmas Lantas by the Kamsel Unit of Grobogan District Police in preventing traffic violations. Data collection techniques include interviews, observation, and document analysis. Data analysis techniques in this research are data collection, data reduction, data presentation, and conclusion drawing. The theory used is POAC management theory and organizational resources (4M). The external and internal factors that influence are also analyzed using SWOT theory. After the research was carried out and the results were found, the cause of traffic violations that increased again was the low level of public awareness due to the implementation of the Dikmas Lantas conducted by the Kamsel Unit of Grobogan Police Station which was still not optimal. The non-optimal implementation of Dikmas Lantas is caused by several factors from outside and inside as well as the Kamsel Unit which pays less attention to management from planning, organizing, implementing to proper control and organizational resources that are still not optimal such as less members, inadequate facilities and infrastructure and the methods used for implementing Dikmas Lantas are not appropriate. Problem solving and solutions are needed in optimizing the activities of the Dikmas Lantas Kamsel Unit in preventing traffic violations in order to realize Kamseltibcar Lantas in the jurisdiction of Grobogan Police.